NANOCAPSULES- A REVIEW - Tinesh Dayaa Rao; Kavitha.S; V.Vishnupriya; Gayathri.R (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The use of nanotechnology in the medical world offers many exciting possibilities. Many techniques are being used today while others are at various stages of testing and research is still going on every day. Nanotechnology within the field of drugs involves applications of nanoparticles which are currently under development, and research that involves the utilization of manufactured nanocapsules to form repairs at the cellular level, and is sometimes referred to as nanomedicine. The applications of nanotechnology in medicine could create a remarkable change in the diagnosis and treatment of disease in the future. Nanocapsules are having exciting applications not only in medicine, but also in other fields. This review was aimed to highlight the important aspects of nanocapsules.